IMPLEMENTASI MANAJEMEN KELAS PADA MATA PELAJARAN PAI KELAS VII DI SMP ISLAM MANBAUL HUDA AL-MUBAROK JABON SIDOARJO - Alif Mustahib Al-Ghifari; Muhammad Hanif; Kukuh Santoso (VICRATINA, 2021)
This study aims to determine the planning, implementation and evaluation of classroom management implementation in 7th grade PAI subjects at the Islamic Junior High School Manbaul Huda Al-Mubarok Jabon Sidoarjo. Collecting research data using the method of observation, interviews and documentation. Likewise, the analysis of research data using descriptive qualitative means interpreting it with descriptive explanations into conclusions regarding the implementation of classroom management in the 7th grade Islamic Religious Education subject at the Islamic Junior High School Manbaul Huda Al-Mubarok Jabon Sidoarjo. Based on the results of the study, it was concluded that class management planning in Islamic Religious Education subjects by compiling a syllabus, annual program, semester program, learning device plan, academic calendar, and minimum completeness criteria to achieve effective learning goals and take steps to determine competence basic principles, selecting teaching materials, planning learning activities, determining learning media, preparing learning evaluations. In the application of classroom management using student disciplinary arrangements, the teacher gives punishments that are not always the same and can be seen from the violations made by students, if the students' reasons can be understood, they will be tolerated, but otherwise they will be punished according to the type of violation. Discipline is planned in positive activities to improve the characteristics of school discipline, so that effectiveness can be realized in increasing the sense of responsibility of school elements.